Students’ higher-order thinking skills: constructing best practices in teaching English during online learning - Niken Emiria Faradella (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
Conducting higher-order thinking skills (HOTS) activities in an English language classroom is a complete task for teachers, especially in the outbreak. Teachers need a careful plan and effective teaching strategies to make the students engage with the HOTS activities to increase their English language skills. The present study aims to investigate best practices of higher-order thinking skills in teaching English during online learning. A qualitative approach with a case study design was employed in this study. Two teachers of senior high schools in Pekalongan, Central Java, Indonesia volunteered to participate. Data were collected through classroom observation, semi-structured interviews, and document analysis. The classroom observation and document analysis were analyzed using thematic analysis. Findings of the study reveal that both teachers constructed best practices of higher-order thinking skills in their teaching and learning process. They eliminated one of the criteria of HOTS and skipped it in some learning processes. The teachers in their classroom activities should incorporate all criteria of HOTS, i.e., analyzing (C4), evaluating (C5), and creating (C6), properly. The lesson plans did not become the guidance in fostering HOTS to their students. This study also portrays the challenges faced by the teachers in constructing HOTS-based activities during online learning.